Chapter 8 Is the EU different? Comparing the diversity of national and EU-level systems of interest organisations - Berkhout, Joost (West European Politics, 2018)
The European Union interest group population is often characterised as being biased towards business and detached from its constituency base. Many scholars attribute this to institutional factors unique to the EU. Yet, assessing whether or not the EU is indeed unique in this regard requires a comparative research design. We compare the EU interest group population with those in four member states: France, Great Britain, Germany and the Netherlands. We diff erentiate system, policy domain and organisational factors and examine their eff ects on interest group diversity. Our results show that the EU interest system is not more biased towards the representation of business interests than the other systems. Moreover, EU interest organisations are not more detached from their constituents than those in the studied countries. Everywhere, business interest associations seem to be better capable of representing their members' interests than civil society groups. These fi ndings suggest that the EU is less of a sui generis system than commonly assumed and imply the need for more fi ne-grained analyses of interest group diversity.